Agro-economic viability from two croppings of broadleaf vegetables intercropped with beet fertilized with roostertree in different population densities - de Andrade Filho , Francisco Cicupira; Queiroga de Oliveira, Eliane; Silva de Lima, Jailma Suerda; Moreira, Joserlan Nonato; Silva, Ítalo Nunes; Anizio Lins, Hamurábi; Cecílio Filho, Arthur Bernardes; Paes Barros Júnior, Aurélio; Bezerra Neto, Francisco (Revista de la Facultad de Ciencias Agrarias UNCuyo, 2020)
The objective of this study was to evaluate the sustainability and agro-economic viability from two croppings of coriander (C) and two of arugula (A) intercropped with beet (B) as a function of roostertree amounts added to the soil in different population densities. The experimental design was a randomized complete block, with treatments arranged in a 4 x 4 factorial scheme with four replications. The treatments resulted from the combination of four amounts of roostertree biomass (6, 19, 32 and 45 t ha-1 on dry basis) with four population densities of coriander, beet and arugula (20C-50B-20A%, 30C-50B-30A%, 40C-50B-40A% and 50C-50B-50A% of the recommended densities in their single crops). The maximum agronomic efficiency of the polyculture of coriander, beet and arugula was obtained with the density of 40C-50B-40A in the amount of 19 t ha-1 roostertree biomass incorporated into the soil. The highest profitability of the polyculture was obtained with the density of 20C-50B-20A (%) in the amount of 45 t ha-1 of this green manure. High agro-economic efficiency can be obtained by cultivating the polyculture of coriander, beet and arugula when well-managed the factors of production, fertilization with roostertree and population densities. Highlights There are agro-economic efficiency and sustainability in the polyculture of coriander-beet-arugula. Population density is an important production factor for obtaining of agro-economic returns. Appropriate management in the coriander-beet-arugula fertilization with roostertree can provide economic revenues.